New Developments in the Pathophysiology and Management of Primary Immune Thrombocytopenia - Althaus, Karina; Faul, Christoph; Bakchoul, Tamam (Hämostaseologie, 2020)
Immune thrombocytopenia (ITP) is an autoimmune disease that is characterized by a significant reduction in the number of circulating platelets and frequently associated with bleeding. Although the pathogenesis of ITP is still not completely elucidated, it is largely recognized that the low platelet count observed in ITP patients is due to multiple alterations of the immune system leading to increased platelet destruction as well as impaired thrombopoiesis. The clinical manifestations and patients' response to different treatments are very heterogeneous suggesting that ITP is a group of disorders sharing common characteristics, namely, loss of immune tolerance toward platelet (and megakaryocyte) antigens and dysfunctional primary hemostasis. Management of ITP is challenging and requires intensive communication between patients and caregivers. The decision to initiate treatment should be based on the platelet count level, age of the patient, bleeding manifestation, and other factors that influence the bleeding risk in individual patients. In this review, we present recent data on the mechanisms that lead to platelet destruction in ITP with a particular focus on current findings concerning alterations of thrombopoiesis. In addition, we give an insight into the efficacy and safety of current therapies and management of ITP bleeding emergencies.
Keywords: platelet immunology; immune thrombocytopenia; autoantibodies; autoimmune diseases